Retail Soda Purchases Decrease and Water Purchases Increase: 6-Year Results From a Community-Based Beverage Campaign - Marlene B. Schwartz, PhD; Glenn E. Schneider, MPH; Ran Xu, PhD; Yoon-Young Choi, PhD; Abiodun T. Atoloye, PhD; Brooke L. Bennett, PhD; Nicolette Highsmith Vernick, MPA; Lawrence J. Appel, MD, MPH (Elsevier, 2022)
Introduction: This study aimed to document the long-term impacts on beverage sales of a 6-year intervention campaign to reduce consumption of sugar-sweetened beverages. Methods: In 2013, a multicomponent intervention campaign designed to reduce the intake of sugary drinks was launched in Howard County, Maryland. A difference-in-differences regression approach was used to compare data on Howard County supermarket beverage sales (in ounces) from 2013 to 2018 with a set of control supermarkets. Outcome variables were average weekly sales by store of top brands of sugar-sweetened beverages (regular soda, sports drinks, fruit drinks) as well as diet soda and 100% juice. Trends in the sales of water products from 2016 to 2018 were estimated separately using a linear regression model. Results: In Howard County, the sales of regular soda, fruit drinks, and 100% juice decreased significantly more than predicted each year. These changes correspond to a 29.7% decrease in sales for regular soda, a 7.5% decrease for fruit drinks, and a 33.5% drop for 100% juice between 2012 and 2018 in Howard County stores. There was a significant trend such that the net reduction in regular soda sales in Howard County stores became larger over time. The amount of plain water sold in Howard County increased significantly from 2016 to 2018. Conclusions: Multicomponent efforts by local government, nonprofit organizations, and other community-based organizations are needed to decrease sugar-sweetened beverage consumption at the population level. Substantial and sustained improvements in retail beverage sales can be achieved through coordinated messaging, community organizing, and targeted advocacy for policy changes.